KARAKTERISTIK MEDIA KOMUNIKASI INOVATIF WAYANG BEBER METROPOLITAN JAKARTA - Guntur Sukoco (MediaKom : Jurnal Ilmiah Komunikasi, 2018)
This research is in the background of the researcher's concern about the existence of wayang beber which is also the culture of the Indonesian nation that is almost extinct, the preservation of wayang beber in Jakarta with the aim of reviving the art of wayang beber show. A community of lovers of wayang beber in the capital city of Jakarta and currently known to the community as WBM (Wayang Beber Metropolitan), trying to preserve the wayang beber. With data collection techniques in the form of observation involved, in-depth interviews as well as secondary data collection through documentation. The result of this research was obtained Knowledge of Innovative Communication Chenel Puppet on Beber Metropolitan Puppet Community in Jakarta and also as the source of Innovation knowledge is Dalang Wayang Beber Metropolitan in this case brother of Samuel. The message delivered is Wayang Sandal Jepit (WANGSIT) and is also an idea of a new figure in puppet in Indonesia. Wayang is made of a garbage that was not initially used, although in use became a means to protect the feet that place under, but used as a medium to become wayang figures. Communication Channels and Social Systems Media Innovations The Wayang Performing Arts is an interpersonal channel because this communication channel is done to get feedback from the audience in the wayang beber performing arts, and this response is one of the signs of communication channel success in wayang beber performing arts. Confirmation of Media Innovation of Puppet Art Performances can also be said as the Effect of all result of their interview concluding to accept the change made by the dalang in Metropolitan Puppet Community and Beber community.Keywords: Communicative Chanel, Symbolic Interactive, Social Construction, Wayang Beber, Metropolitan Beber Wayang Community, and Wayang Sandal Jepit